A multi-phase project to develop a patient-reported measure of barriers to antiretroviral therapy adherence for use in HIV care: The 7-Item I-Score - Kim Engler; David Lessard; Serge Vicente; Darrell H. S. Tan; Karine Lacombe; Bertrand Lebouché (PLoS ONE, 2026)
Adherence to antiretroviral therapy (ART) is a priority in HIV care. Our goal was to develop and validate a new, short patient-reported outcome measure to screen for barriers to daily oral ART adherence in HIV care in Canada and France. The overarching design was that of a multi-phase, multi-site instrument development project. It involved a previously published qualitative research synthesis (to develop a conceptual framework from which to generate items). Here, we present the results of cognitive interviews (for content validity testing of the preliminary items) and of a longitudinal survey-based study where the revised 7-item instrument (the I-Score) was administered at two timepoints (baseline, 4 weeks), along with five indirect measures of ART adherence, including self-reported HIV viral load and, for a subset of Montreal participants, plasma viral load. The survey data was used to analyze the instrument’s measurement properties, namely structural validity (e.g., with Pearson inter-item correlations); construct validity, including cross-cultural validity, for a variety of sociodemographic groups (with receiver operating curve (ROC) analyses and areas under the curve (AUC); reliability (with the intraclass correlation coefficient (ICC)); and measurement error (with the standard error of measurement (SEM)). Study participants were adults living with HIV on antiretroviral therapy recruited from hospital-based infectious disease centers and community-based organizations in Montreal, Toronto, and Paris. The qualitative synthesis of 41 studies led to a framework composed of 6 barrier domains. One item was generated per domain. The 6-item measure was submitted to cognitive testing with 12 adults living with HIV, leading to several changes, including the division of one item into two, creating a 7-item measure. Overall, 305 adults living with HIV participated in the survey. Inter-item correlations were low to moderate, suggesting no redundant items. Among conclusive results, AUC’s were all above the predefined threshold (≥ 0.70) for self-reported viral load and plasma viral load for the global sample and across all subgroups examined. The ICC, at 0.81, was also above the predefined threshold (≥ 0.70). The SEM was 0.43. Overall, the evidence generated supports the 7-item I-Score measure’s content validity, construct validity/cross-cultural validity, reliability, and acceptable measurement error, in its specified context of use.